PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPOSISI MENGGUNAKAN MODEL CONCEPT SENTENCE DI KELAS V SDN 13 BATU GADANG KOTA PADANG - Meisyah Azzahra, Dinda; Sukma, Elfia; Adrias, Adrias; Chandra, Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low writing skills of fifth-grade students in composing exposition texts at SDN 13 Batu Gadang, Padang, as indicated by an average score of 63 with only 20% of students achieving mastery. The purpose of this research was to improve students’ exposition writing skills through the implementation of the Concept Sentence model. This study employed Classroom Action Research (CAR) consisting of two cycles, each including planning, action, observation, and reflection stages. The subjects were 25 fifth-grade students. Data were collected through observation and writing tests, and analyzed using qualitative and quantitative approaches. The results showed a significant improvement in students’ writing skills. The average score increased from 59.57 in the first meeting of Cycle I to 80.54 in the second meeting of Cycle I, and further improved to 87.85 in Cycle II. The percentage of learning mastery also increased from 20% to 80%. In addition, teacher and student activities showed improvement in each cycle. Thus, the Concept Sentence model is proven effective in improving students’ exposition writing skills in elementary school.